2023
DOI: 10.1084/jem.20221086
|View full text |Cite
|
Sign up to set email alerts
|

Secreted mammalian DNases protect against systemic bacterial infection by digesting biofilms

Abstract: Extracellular DNase DNASE1L3 maintains tolerance to self-DNA in humans and mice, whereas the role of its homolog DNASE1 remains controversial, and the overall function of secreted DNases in immunity is unclear. We report that deletion of murine DNASE1 neither caused autoreactivity in isolation nor exacerbated lupus-like disease in DNASE1L3-deficient mice. However, combined deficiency of DNASE1 and DNASE1L3 rendered mice susceptible to bloodstream infection with Staphylococcus aureus. DNASE1/DNASE1L3 double-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 87 publications
2
18
0
Order By: Relevance
“…Because of their enrichment in the SED in a region between sampled microbiota and the host we propose that DNASE1L3 and C1q are involved in management of bacteria sampled from the gut lumen. In particular, potential for high concentration of secreted DNASE1L3 in the SED is consistent with it having a role in digestion of bacterial DNA as observed previously in other contexts 50 . Bacterial DNA could be potentially pathogenic and could drive aberrant activity of DN2 B cells that are situated together with the DNASE1L3- expressing DC 20 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Because of their enrichment in the SED in a region between sampled microbiota and the host we propose that DNASE1L3 and C1q are involved in management of bacteria sampled from the gut lumen. In particular, potential for high concentration of secreted DNASE1L3 in the SED is consistent with it having a role in digestion of bacterial DNA as observed previously in other contexts 50 . Bacterial DNA could be potentially pathogenic and could drive aberrant activity of DN2 B cells that are situated together with the DNASE1L3- expressing DC 20 .…”
Section: Discussionsupporting
confidence: 87%
“…However, here we show that DNASE1L3 is not expressed in the GC in human GALT, tonsil or lymph node but is located in the SED. DNASE1L3 is found both intra- and extracellularly, can digest bacterial DNA and even contribute to the disruption of biofilm 50 . Mouse models have contributed in many ways to the current view of the relationship between apoptosis and lupus pathogenesis, yet much data may not be translationally relevant because of the marked species difference in the distribution of DNASE1L3 that we identify here 56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although deletion of an upstream fragment (∆32-43) had no impact on abscess size, deletion of the center gene block (∆44-57) eliminated the skin abscess phenotype (Figures 1C-D). These data localized skin abscess candidates to 14 genes (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) in mΦ11 for further analysis. Of the 14 genes, eight gene sequences were unrelated to prototypical Φ11 or other known prophages and therefore were considered promising candidates for further analysis (Table S1).…”
Section: Genetic Deletions Localize the Mφ11 Gene(s) Responsible For ...mentioning
confidence: 93%
“…Related studies have reported that DNase I can kill bacteria and inhibit bacterial biofilm formation by cleavage of DNA. 31 Based on the photothermal bactericidal effect of MPDA and the antibacterial effect of Zn 2+ and DNase I, the nanosystem prepared in this study is expected to achieve efficient bacterial killing and effective biofilm removal under mild NIR irradiation. In addition, based on the unique paraben structure of MPDA, the system has excellent ROS scavenging ability, which can effectively reduce/mitigate oxidative stress damage at the trauma site and accelerate the damage repair process.…”
Section: Introductionmentioning
confidence: 99%